2006
DOI: 10.1002/hep.21273
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis C: Dosage and compliance

Abstract: The HEP-NET study recently published in HEPATOLOGY 1 showed that a 24-week course of PEG-IFN (1.5 g/Kg/weekly) alpha-2b was associated with a SVR of 71% in patients with acute hepatitis C (AHC). Treatment was initiated after spontaneous viral clearance ("late-treatment") was excluded and the SVR rate was similar to that we achieved with a 12-week regimen of PEG-IFN alpha-2b administered without waiting for the spontaneous viral clearance ("early treatment"). 2 Compliance in the HEP-NET study was a major issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…We report our results from a unique center and emphasize how IDUs are handled in our regional referral system. The design of the studies published to date that compare a 12-week regimen with a 24-week regimen is not going to resolve the issue of early-versus late-treatment strategies, especially if the studies include different percentages of IDUs [17]. These studies simply show that SVR is significantly associated with a high dose of pegylated IFN administered during early treatment in the 12-week course, whereas SVR is significantly affected by the lower compliance rate associated with the late-treatment strategy of the 24-week regimen [12].…”
Section: Discussionmentioning
confidence: 97%
“…We report our results from a unique center and emphasize how IDUs are handled in our regional referral system. The design of the studies published to date that compare a 12-week regimen with a 24-week regimen is not going to resolve the issue of early-versus late-treatment strategies, especially if the studies include different percentages of IDUs [17]. These studies simply show that SVR is significantly associated with a high dose of pegylated IFN administered during early treatment in the 12-week course, whereas SVR is significantly affected by the lower compliance rate associated with the late-treatment strategy of the 24-week regimen [12].…”
Section: Discussionmentioning
confidence: 97%
“…While studies have shown that treatment during the acute phase can achieve high (72%–98%) success rates [1][9], the optimal regimen and timing of treatment are still a matter of debate [10][13]. One crucial issue that remains to be resolved is whether physicians should treat all patients diagnosed with acute hepatitis C, or should wait and treat only those who failed to clear the virus in the first few months after infection.…”
Section: Introductionmentioning
confidence: 99%